INSTITUSIONALISASI AKUNTANSI SOSIAL PADA PERUM PERHUTANI BLITAR - Nurdiwaty, Diah; Djamhuri, Ali; Kamayanti, Ari (Faculty of Economics and Business, University of Muhammadiyah Malang, 2014)
This study was attempted to describe the institutionalization of social accounting in Indonesian Forestry Company housing in Blitar. This project was a qualitative research which applied case study as the method in order to comprehend the institutionalization of social accounting in Indonesian Forestry Company housing in Blitar in which the liability of its social activities was PKBL (Partnership and Environment Development Program). The results revealed that the social accounting institutionalization process in this program experienced no significant problems; instead, the management provided great supports to the implementation of this program, such as organizing a reconstruction program every month, arranging training program for PKBL staff. In addition, this program encouraged the implementation of new beneficial policies, such as the guarantee provision on PKBL loan for customers and the customers’ exclusion in life insurance. Nevertheless, some documents or regulations concerning the implementation of PKBL activities could not be found completely in this study.